2019
DOI: 10.1007/s10750-019-04016-z
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of surrounding land-use on mussel growth and glycogen levels in the St. Croix and Minnesota River Basins

Abstract: Freshwater mussels face threats from climate change and changing land use that are dramatically altering their habitat. The health of mussel populations and the state of current and past environmental conditions can be monitored by measuring mussel growth and glycogen levels. In this study, we measured growth and glycogen levels in mussels from two small river basins impacted by different land uses. The Snake River in the St. Croix Basin, Minnesota, had low levels of suspended sediments and was surrounded most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 94 publications
3
7
0
Order By: Relevance
“…While we investigated different river basins, where mussels often have different growth characteristics, we found similar L ∞ for female L. cardium mussels to those measured in Hornbach et al. (2021), although the L ∞ for A. plicata and male L. cardium from our rivers were much smaller (Figure S2; Table 2). This underestimation in potential maximum size might be due to our collection methods.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…While we investigated different river basins, where mussels often have different growth characteristics, we found similar L ∞ for female L. cardium mussels to those measured in Hornbach et al. (2021), although the L ∞ for A. plicata and male L. cardium from our rivers were much smaller (Figure S2; Table 2). This underestimation in potential maximum size might be due to our collection methods.…”
Section: Discussionsupporting
confidence: 82%
“…For a resampled site in the Kiamichi River in Oklahoma (K2), the median A. plicata L ∞ in our study is 10 mm smaller than the median reported in Sansom et al (2016), although their value falls within the 60% credible interval of our estimated value. While we investigated different river basins, where mussels often have different growth characteristics, we found similar L ∞ for female L. cardium mussels to those measured in Hornbach et al (2021), although the L ∞ for A. plicata and male L. cardium from our rivers were much smaller (Figure S2;…”
Section: )supporting
confidence: 58%
See 3 more Smart Citations